Correction: Free ion diffusivity and charge concentration on cross-linked polymeric ionic liquid iongel films based on sulfonated zwitterionic salts and lithium ions. Issue 2 (6th January 2021) - Valverde, David; Garcia-Bernabé, Abel; Andrio, Andreu; García-Verdugo, Eduardo; Luis, Santiago V.; Compañ, Vicente
Abstract : Correction for 'Free ion diffusivity and charge concentration on cross-linked polymeric ionic liquid iongel films based on sulfonated zwitterionic salts and lithium ions' by David Valverde et al., Phys. Chem. Chem. Phys., 2019, 21, 17923–17932, DOI: ; 10.1039/C9CP01903K .